Analysis Of Kepler-71 Activity Through Planetary Transit. Issue Volume 12:Issue S328(2016) (12th September 2017) - Gusmão, Eber A.; Selhorst, Caius L.; Oliveira, Alexandre S.
Abstract: An exoplanet transiting in front of the disk of its parent star may hide a dark starspot causing a detectable change in the light curve, that allows to infer physical characteristics of the spot such as size and intensity. We have analysed the Kepler Space Telescope observations of the star Kepler-71 in order to search for variabilities in 28 transit light curves. Kepler-71 is a star with 0.923 M ⊙ and 0.816 R ⊙ orbited by the hot Jupiter planet Kepler-71b with radius of 1.0452 R J . The physical parameters of the starspots are determined by fitting the data with a model that simulates planetary transits and enables the inclusion of spots on the stellar surface with different sizes, intensities, and positions. The results show that Kepler-71 is a very active star, with several spot detections, with a mean value of 6 spots per transit with size 0.6 R P and 0.5 I C, as a function of stellar intensity at disk center (maximum value).